The Power of a Parent's Touch: Evaluation of Reach and Impact of a Targeted Evidence-Based YouTube Video. Issue 4 (October 2017) - Campbell-Yeo, Marsha; Dol, Justine; Disher, Timothy; Benoit, Britney; Chambers, Christine T.; Sheffield, Kaitlyn; Boates, Talia; Harrison, Denise; Hewitt, Brenda; Jangaard, Krista; Stinson, Jennifer; Taddio, Anna; et al.
Abstract : Despite strong evidence that skin-to-skin contact and breast-feeding are effective pain-relieving interventions for infants undergoing painful procedures, they remain underutilized in clinical practice. Given the important contribution of parents, there is a need to find innovative ways to assist parents to become actively involved in their infant's care. We developed a YouTube video to disseminate evidence-based information on the effectiveness of skin-to-skin contact and breast-feeding for infant pain management. The 2-minute 39-second video launched on December 2, 2014, and was promoted through Web-based and in-person communication and YouTube advertisements. Data were collected using YouTube analytics and an online survey. Post–18 months from its launch, the video had a reach of 157 938 views from 154 countries, with most viewers watching an average of 73% of the video (1 minute 56 seconds). Parents ( n = 32) and healthcare providers ( n = 170) completed the survey. Overall, both reported that they liked the video, found it helpful, felt more confident, and were more likely to use skin-to-skin contact (16% and 12%) and breast-feeding (3% and 11%), respectively, during future painful procedures. Despite the high-viewing patterns, alternative methods should be considered to better evaluate the impact on practice change. Abstract : Supplemental Digital Content is Available in the Text.